The effectiveness of Duolingo's AI-powered language learning platform in improving second language acquisition among Malaysia's tertiary students - Oh, Fang Yan (2024)
The purpose of this study was to investigate the aspects of Duolingo that might improve Malaysian tertiary students' acquisition of a second language. The enhancement of second language learning is the dependent variable in this research study, and the independent variables - perceived ease of use, perceived usefulness, motivation, and perceived social influence - will be taken into consideration as the elements influencing this variable. Students in tertiary education who are at least 16 years old will be our target demographic. Using the convenience sampling approach, we administered the questionnaire to our target group in 200 sets overall.